Analisis Penggunaan Bahasa Non Verbal Dominan dalam Komunikasi Anak Tunarungu - Marsia Sumule Genggong; Gista Yanuarti (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2014)
The study was carried out at SLB Mandara Kendari. The purpose of the study is to find the form of the dominant language use non verbal in communicating of the Deaf children. Theoretically, this study aims to enrich the treasure of knowledge, especially of communications knowledge, methodological study used as a reference for further researchers, especially those related to the discussed material. Practically, this study aims to inform parents who have Deaf child in order they know how to communicate through nonverbal communication. The method used in this research is descriptive qualitative which applied purposive sampling with seven informants of Deaf children and two teachers as additional informants and theories that used were Kinesic Theory of Ray Birdwhistell. The finding of this study showed that the form of the dominant language used of nonverbal Deaf children communication were gesture and facial expressions. The form of nonverbal communication was the most effective used because the symbol they used were very straight forward, assertive, and clear for communicating with the teacher and the surroundings. Moreover, by using body language and facial expressions as a whole was quickly accepted by deaf children and their environment. Keywords: non-verbal language, deaf